2009
DOI: 10.1185/03007990903116875
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric allergy medications: review of currently available formulations

Abstract: Treatment for AR is often long-term, particularly in persistent AR; therefore, safety, tolerability, convenience, and patient/parental acceptance are important considerations when deciding which medication to prescribe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 96 publications
0
5
0
2
Order By: Relevance
“…Current European Parliament legislation12 also emphasises the importance of making new drugs more acceptable. However, palatability comes at a price as the taste of traditionally unpalatable drugs has commonly been disguised with sugar 13. Regulatory agencies and professional organisations in Europe and the USA have recommended avoidance of sugar in paediatric medicines and many artificial sweeteners have been substituted, but sweeteners themselves may also have associated adverse effects 13…”
Section: Adherence and Tastementioning
confidence: 99%
“…Current European Parliament legislation12 also emphasises the importance of making new drugs more acceptable. However, palatability comes at a price as the taste of traditionally unpalatable drugs has commonly been disguised with sugar 13. Regulatory agencies and professional organisations in Europe and the USA have recommended avoidance of sugar in paediatric medicines and many artificial sweeteners have been substituted, but sweeteners themselves may also have associated adverse effects 13…”
Section: Adherence and Tastementioning
confidence: 99%
“…Por muito tempo os excipientes foram descritos como substâncias inertes que não apresentavam ação farmacológica ou efeito toxicológico e, dessa maneira, nunca eram levados em consideração quando um paciente apresentava reações adversas. No entanto, sabe-se que estes compostos podem afetar diretamente o perfil de segurança dos medicamentos, podendo ser responsáveis por inúmeros efeitos adversos (SCADDING, 2009).…”
Section: Adverse Effects Public Health Excipientsunclassified
“…Although the H 1 -antihistamines are commonly used for the treatment of both AR and chronic idiopathic urticaria (CIU) in children, recent reviews have indicated that, in comparison with adults, only a limited number of trials of these agents have been conducted primarily in children with AR, and that data from well-designed trials in children are generally lacking [38,43,51]. There are many reasons for lack of data in children.…”
Section: Management Of Ar In Paediatric Patientsmentioning
confidence: 99%
“…There are many reasons for lack of data in children. Besides the considerable and challenging ethical considerations of conducting trials in patients too young to give consent themselves [38,43], there are often difficulties in enrolling children into clinical trials because of the parents’ and physicians’ concerns about the potential side effects of the active ingredients as well as other ingredients such as sugar and excipients in medicines [43,51]. Conversely, parental concern about the lack of symptom relief if the child was randomised to the placebo group also plays a vital role in parents not wishing to enrol their children in placebo-controlled studies [43].…”
Section: Management Of Ar In Paediatric Patientsmentioning
confidence: 99%